Association of season of birth with DNA methylation and allergic disease. Issue 9 (29th March 2016) - Lockett, G. A.; Soto‐Ramírez, N.; Ray, M. A.; Everson, T. M.; Xu, C.‐J.; Patil, V. K.; Terry, W.; Kaushal, A.; Rezwan, F. I.; Ewart, S. L.; Gehring, U.; Postma, D. S.; et al.
Abstract: Background: Season of birth influences allergy risk; however, the biological mechanisms underlying this observation are unclear. The environment affects DNA methylation, with potentially long‐lasting effects on gene expression and disease. This study examined whether DNA methylation could underlie the association between season of birth and allergy. Methods: In a subset of 18‐year‐old participants from the Isle of Wight (IoW) birth cohort ( n = 367), the risks of birth season on allergic outcomes were estimated. Whole blood epigenome‐wide DNA methylation was measured, and season‐associated CpGs detected using a training‐and‐testing‐based technique. Validation method examined the 8‐year‐old Prevention and Incidence of Asthma and Mite Allergy (PIAMA) cohort. The relationships between DNA methylation, season of birth and allergy were examined. CpGs were analysed in IoW third‐generation cohort newborns. Results: Autumn birth increased risk of eczema, relative to spring birth. Methylation at 92 CpGs showed association with season of birth in the epigenome‐wide association study. In validation, significantly more CpGs had the same directionality than expected by chance, and four were statistically significant. Season‐associated methylation was enriched among networks relating to development, the cell cycle and apoptosis. Twenty CpGs were nominally associated with allergic outcomes. Two CpGs were marginally on the causal pathway to allergy. Season‐associated methylation was largely absent in newborns, suggesting it arises post‐natally. Conclusions: This study demonstrates that DNA methylation in adulthood is associated with season of birth, supporting the hypothesis that DNA methylation could mechanistically underlie the effect of season of birth on allergy, although other mechanisms are also likely to be involved.